2006
DOI: 10.1289/ehp.8115
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Assessing Infectious Disease Risks from Bathing in Fresh Recreational Waters in Relation to the Concentration of Escherichia coli , Intestinal Enterococci, Clostridium perfringens , and Somatic Coliphages

Abstract: We performed epidemiologic studies at public freshwater bathing sites in Germany to provide a better scientific basis for the definition of recreational water quality standards. A total of 2,196 participants were recruited from the local population and randomized into bathers and non-bathers. Bathers were exposed for 10 min and had to immerse their head at least three times. Water samples for microbiological analysis were collected at 20-min intervals. Unbiased concentration–response effects with no-observed-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 12 publications
(29 reference statements)
3
98
0
8
Order By: Relevance
“…Three of them only studied F-specific phages, and while Lee et al and Wade et al found some correlation [147,148], Van Asperen et al did not [149]. Wiedenmann et al only studied somatic coliphages and found some correlation [150]. In the studies where both phages were tested, the results are incongruent, since Von Schirnding et al failed to show any correlation with either somatic or F-specific phages [151], Colford et al found a correlation with F-specific phages [152], and Abdelzaher et al found a correlation with somatic coliphages [145].…”
Section: Relationship To Health Riskmentioning
confidence: 99%
“…Three of them only studied F-specific phages, and while Lee et al and Wade et al found some correlation [147,148], Van Asperen et al did not [149]. Wiedenmann et al only studied somatic coliphages and found some correlation [150]. In the studies where both phages were tested, the results are incongruent, since Von Schirnding et al failed to show any correlation with either somatic or F-specific phages [151], Colford et al found a correlation with F-specific phages [152], and Abdelzaher et al found a correlation with somatic coliphages [145].…”
Section: Relationship To Health Riskmentioning
confidence: 99%
“…Clostridium perfringens spores have been recommended as potentially more useful surrogates for protozoan pathogens such as Cryptosporidium and Giardia and for monitoring impacts of discharges on receiving waters (Medema et al 1997b;Lisle et al 2004;Wiedenmann et al 2006). In the present study, C. perfringens concentrations were determined using the multiple-tube fermentation method with iron milk medium as substrate (St John et al 1982;AOAC 1995).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Both types of coliphage have been recommended as surrogates for human enteric viruses (Havelaar et al 1993;Wiedenmann et al 2006). Samples for male-specific coliphage analysis were combined with tryptic soy agar supplemented with streptomycin-ampicillin and E. coli F amp as a host and poured into Petri dishes to solidify.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…According to Payment and Franco (3), Clostridium perfringens is a suitable indicator of human enteric viruses, Giardia cysts, and Cryptosporidium oocysts in finished water and can also be used in the assessment of water treatment processes due to the resistance of Clostridium spores to chlorine. Furthermore, the presence of C. perfringens in water is also associated with fecal contamination, and it has been evaluated and utilized as an alternative indicator of fecal pollution (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Thus, a simple and reliable culture-based method to isolate and enumerate C. perfringens, the membrane filtration method on mCP agar, has been elaborated and evaluated to monitor the presence of C. perfringens in water (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%